Azithromycin for the Treatment of Eosinophilic Nasal Polyposis: Clinical and Histologic Analysis. Issue 2 (June 2016) - de Oliveira, Isamara Simas; Crosara, Paulo Fernando Tormin Borges; Cassali, Geovanni Dantas; dos Reis, Diego Carlos; Rodrigues, Danilo Santana; Nunes, Flavio Barbosa; Guimarães, Roberto Eustáquio Santos
Introduction: Macrolides used as immunomodulators are a promising tool for chronic inflammatory airway diseases. Eosinophilic nasal polyposis (ENP) is still considered a disease that is difficult to control with the currently standardized treatments. Objectives: To evaluate prolonged treatment with low-dose azithromycin for ENP based on clinical and histopathologic variables. Methods: The present investigation was a self-paired case study of 33 patients with ENP. A comparison was performed between patients before and after treatment with azithromycin for 8 weeks. The patients were subjected to clinical examinations, staging (three-dimensional imaging by endoscopy), application of the questionnaire, and biopsy of nasal polyps at the beginning and at the end of the treatment. Results: The treatment yielded a clinical improvement regarding the two variables studied: polyposis staging (69.7%) and questionnaire (57.6%). We did not find significant differences in the inflammatory pattern and in the percentage or absolute number of eosinophils per field between samples obtained before and after the treatment (p > 0.05). There was no difference between the answers obtained from groups with and without asthma and/or aspirin intolerance (p > 0.3). The patients with advanced initial staging exhibited lower subjective improvement index and staging reduction (p = 0.031 and p = 0.012, respectively). Conclusion: Based on this study, azithromycin may be considered as another therapeutic option for ENP. However, further studies are necessary to define the real mechanism of action involved.